2021
DOI: 10.1038/s41598-021-89604-7
|View full text |Cite
|
Sign up to set email alerts
|

A computational model for predicting changes in infection dynamics due to leakage through N95 respirators

Abstract: In the absence of fit-testing, leakage of aerosolized pathogens through the gaps between the face and N95 respirators could compromise the effectiveness of the device and increase the risk of infection for the exposed population. To address this issue, we have developed a model to estimate the increase in risk of infection resulting from aerosols leaking through gaps between the face and N95 respirators. The gaps between anthropometric face-geometry and N95 respirators were scanned using computed tomography. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Particularly when talking, the number of particles captured by the mask increased at a rate of about 5% per L/min [ 45 ], suggesting that less aerosol was leaked. Similar conclusions were drawn by Hariharan et al, who investigated the particle leakage with different respirators, measuring a reduction from 17–22% to 4% when the flow rate was increased from 10 L/min to 70 L/min [ 46 ]. Tang et al studied the turbulent jet caused by coughing and suggested that, according to the typology of the mask worn, it is possible to thwart the trajectory of the jet, directing airflow towards the boundaries of masks with poor fit [ 47 ].…”
Section: Discussionsupporting
confidence: 83%
“…Particularly when talking, the number of particles captured by the mask increased at a rate of about 5% per L/min [ 45 ], suggesting that less aerosol was leaked. Similar conclusions were drawn by Hariharan et al, who investigated the particle leakage with different respirators, measuring a reduction from 17–22% to 4% when the flow rate was increased from 10 L/min to 70 L/min [ 46 ]. Tang et al studied the turbulent jet caused by coughing and suggested that, according to the typology of the mask worn, it is possible to thwart the trajectory of the jet, directing airflow towards the boundaries of masks with poor fit [ 47 ].…”
Section: Discussionsupporting
confidence: 83%
“…Similar observations were reported for breathing, coughing and sneezing by using human subjects [ 24 , 33 , 50 ], manikin model [ 22 , 23 , 39 , 53 ] or CFD models [ 26 ]. Furthermore, leakages were also found for KN95 or N95 masks [ 25 , 42 , 55 , 56 ]. Especially in closed rooms without effective ventilation, exhaled aerosol particles can accumulate and develop a critical concentration if single persons are infected.…”
Section: Discussionmentioning
confidence: 99%
“…These values are subsequently summed to calculate the leakage gap surface area. 8,13 The following measures are used to assess the fit for various frame designs (1) contact gap profile between the face mask and the headform and (2) surface area of the leakage gap created due to imperfect fit.…”
Section: Methodsmentioning
confidence: 99%